1997
DOI: 10.1016/s0042-6989(96)00113-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spatial frequency and field size on the spread of exclusive visibility in binocular rivalry

Abstract: We measured binocular rivalry between dichoptic, orthogonal, sinusoidal gratings both having spatial frequencies of 0.5, 1, 2, 4, 8 or 16 c deg-1 in fields ranging from 0.5 to 8 deg of visual angle in diameter. Total time that one or the other grating was exclusively visible had an inverted U-shaped relationship with spatial frequency, with the peak shifting to coarser spatial frequencies as the field size increased. We computed for each spatial frequency the maximum field size over which a criterion duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 12 publications
5
53
3
Order By: Relevance
“…Several experiments have reported that exclusivity (the amount of time spent in a stable percept) decreases as a function of stimulus size ( Figure 4A; Blake et al, 1992;O'Shea et al, 1997). We simulated this finding by manipulating the proportion of the retinal images occupied by the stimuli.…”
Section: Piecemeal Rivalry and Traveling Wavesmentioning
confidence: 93%
“…Several experiments have reported that exclusivity (the amount of time spent in a stable percept) decreases as a function of stimulus size ( Figure 4A; Blake et al, 1992;O'Shea et al, 1997). We simulated this finding by manipulating the proportion of the retinal images occupied by the stimuli.…”
Section: Piecemeal Rivalry and Traveling Wavesmentioning
confidence: 93%
“…3). The purpose of these observations was to ask whether the variables, both of which are known to influence the alternation rate in binocular rivalry (8,13; see also below), affect the alternation rates measured in normal binocular view. Changing these parameters does indeed affect the rate in normal view.…”
Section: Fluctuations In Perception During Normal Binocular Viewingmentioning
confidence: 99%
“…In the fovea, the zone of suppression may be on the order of 10-15 arcmin 17 , which increases with eccentricity 18 , with the spatial scale (i.e., inversely with spatial frequency) of the stimulus 19,20 , and with decreasing light level 21 . Such zones of suppression within an eye may show synchronized alternations if the stimuli in the visual field possess a common configuration or a common color 22,23 , which suggests the existence of a cooperative network underlying the binocular rivalry process 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Factors that increase stimulus strength include: contour density 32 , luminance level 33 , contrast level 34 , middle spatial frequencies 34,35 , size 19 , and velocity 36,37 . In general, a stronger stimulus shows greater predominance during rivalry, where predominance is defined as the total proportion of time a stimulus is visible 13 .…”
Section: Introductionmentioning
confidence: 99%